Occupational stress in Portuguese police officers - Guimarães, Teresa (2016)
Background - Occupational stress occurs when individuals perceive work demands as exceeding their resources and abilities to cope with them, inducing a set of physical and emotional responses and affecting job satisfaction. Policing is often associated with high levels of occupational stress, resulting from stressors found in the work environment and in the individual’s family life. Objectives - To assess perceived occupational stress levels in police officers and to identify the most relevant stressors. Methods - Fifteen (15) police officers (from a police station with 45 professionals), 93.3 % males, 24 - 46 years (M = 33.27; SD = 6.24), with an average of 9.07 years of experience (SD = 6.72), 66.7 % working more than 40 hours/week and 86.7 % doing shift work, completed the “Operational Police Stress Questionnaire” (PSQ-Op) and the “Organizational Police Stress Questionnaire” (PSQ-Org). Results - Participants presented moderate stress levels for PSQ-Org (M = 3.45; SD = 1.18) and PSQ-Op (M = 3.62; SD = 1.01), with no significant differences between scores. No significant differences were found in stress levels regarding demographic or job variables. Main sources of stress are related to lack of resources, bureaucracy, working hours, shift work, the risk of being injured or witnessing traumatic events. Conclusions - Our findings suggest a perception of moderate level of occupational stress in police officers, both at organizational and operational level. The fact that even moderate-intensity stressors affect individuals in a chronic way and may elicit physical and emotional responses, affecting health and well-being, strengthens the importance of interventions that enhance police officers’ ability to cope with stressors, helping to preserve job satisfaction and quality of life.